Pengaruh Beban Kerja Dan Keadilan Reward Terhadap Burnout Dengan Job Security Sebagai Variabel Moderating Di Rumah Sakit Umum Daerah Ratu Zalecha - Khairunnisa Khairunnisa; Zakhyadi Ariffin; Rini Rahmawati; Meiske Claudia; Dahniar Dahniar (Jurnal Kesehatan Indonesia, 2025)
Burnout, a form of physical, mental, and emotional exhaustion that occurs more frequently among medical and paramedical personnel than among other personnel, remains a common problem. Indications of burnout can be caused by excessive workloads, inappropriate reward systems, or concerns about job security. This study aims to analyze the influence of workload and reward fairness on burnout with job security as a moderating variable at Ratu Zalecha Martapura Regional General Hospital. The design of this study used a qualitative research with a correlational approach based on explanatory research. The data collection was cross-sectional using a questionnaire to the research sample, namely some of the paramedics in the inpatient ward of Ratu Zalecha Martapura Regional Hospital. The sample selection used a probability sampling method (proportional stratified random sampling) in 9 inpatient wards with a PNS: PTT ratio of 5:3 and the accumulated results were 139 paramedics. The measurement analysis used was Partial Least Square (PLS). The result of this indicated that (i) there was a positive significant influence workload on burnout, (ii) there was a negative significant influence justice reward on burnout, (iii) there was an interaction of job security as the monitoring variable to the influence of workload on burnout, (iv) there was an interaction of job security as the monitoring variable the influence of justice reward on burnout. Conclusion, there is an influence of workload and reward fairness on burnout with job security as a moderating variable at Ratu Zalecha Regional General Hospital.